Corporate Debt Restructuring An Evaluation Of Approaches Adopted In Malaysia - Hoe, Kwok Yew (2002)
This research examines the debt restructuring methods of Corporate Debt Restructuring Committee(CDRC, and its impact upon twenty one public-listed companies which have been referred to it. It sis found that there is a significant difference between the performance of these companies and leading companies in their respective industries, measured by changes in the pre-crisis period and post-crisis period.